Preparation and Performance Analysis of High-Viscosity and Elastic Recovery Modified Asphalt Binder - Liangchen Qu; Yingli Gao; Hui Yao; Dandan Cao; Ganpeng Pei; Bei He; Kairui Duan; Wenjuan Zhou (Advances in Civil Engineering)
This study presented the preparation and performance of a kind of high viscosity and elastic recovery asphalt (HVERA) by using some modifiers. The performance of styrene-butadiene-styrene (SBS), rock asphalt (RA), crumb rubber (CR), and stabilizing agent (SA) for different modifiers was investigated by conventional binder test. Effects of modifiers on the high- and low-temperature properties of HVERA were investigated. The dynamic viscosity (DV) test, dynamic shear rheometer (DSR), and bending beam rheometer (BBR) analysis indicated that the high- and low-temperature rheological properties of asphalt were improved attribute to the addition of mixture of modifiers. Meanwhile, the short-term aging and long-term aging were simulated by rolling thin film oven (RTFO) and pressure aging vessel (PAV) tests. Furthermore, the Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) measurements were conducted for obtaining the mechanism and microstructure distribution of the modified asphalt binders. From the test results in this study, it was evident that the addition of SBS, RA, CR, and SA into a neat asphalt binder could both significantly improve the viscosity of the binder at high temperature and lower the creep stiffness at low temperature, which was beneficial to better both high-temperature stability and low-temperature cracking resistance of asphalt pavements. It was proved that the high temperature grade of HVERA could be increased by increasing of RA and a proper percentage of modifiers could be improved by the low temperature grade of HVERA.